Motivational Achievement Relationship and Procrastination Academic - Sefni Rama Putri; Ilham Khairi Siregar (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2019)
Research studies on the low motivation of achievement of students towards the high degree of academic procrastination in the course of lectures. The research aims to get a motivational depiction of student study and counseling studies Program and get an overview of student academic procrastination. This research sample is a tutoring and counseling student amounting to 75 people using a random aiming technique. The instrument used is the motivation scale of achievement and academic procrastination. Furthermore, the prerequisite tests include test normality and linierity testing, as well as simple regression analyses. Based on the analysis results obtained an R value of -0.252 which shows the regression coefficient between achievement motivation and students' procrastination with an R-Square value of -0.063. This shows that achievement motivation is negatively related to academic procrastination of 6%. In line with the research results that high achievement motivation can decrease students academicprocrastination in lecturing